(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
An important factor influencing employee engagement is corporate social responsibility, or CSR. Studies reveal that CSR programs allow workers to contribute more of their entire self to the workplace, which strengthens their sense of loyalty and belonging to the company. The connection between CSR and employee engagement in firms is further examined, showing how the two are positively correlated. To further illuminate the relationship between CSR and engagement levels, studies of executive and management level personnel are conducted to determine the influence of CSR on various organizational levels. Insights into the practical aspects of CSR and its effects on engagement are also provided by examining the ramifications of CSR activities on employee engagement in a sample of Indian enterprises. Lastly, a direct relationship has been shown in large-scale companies between CSR and employee engagement, highlighting the significance of CSR in encouraging employee commitment.